Exercise training and artery function in humans: nonresponse and its relationship to cardiovascular risk factors - Green, D.; Eijsvogels, T.; Bouts, Y.; Maiorana, Andrew; Naylor, L.; Scholten, R.; Spaanderman, M.; Pugh, C.; Sprung, V.; Schreuder, T.; Jones, H.; Cable, N.T.; et al. (The American Physiological Society, 2014)
The objectives of our study were to examine 1) the proportion of responders and nonresponders to exercise training in terms of vascular function; 2) a priori factors related to exercise training-induced changes in conduit artery function, and 3) the contribution of traditional cardiovascular risk factors to exercise-induced changes in artery function. We pooled data from our laboratories involving 182 subjects who underwent supervised, large-muscle group, endurance-type exercise training interventions with pre-/posttraining measures of flow-mediated dilation (FMD%) to assess artery function. All studies adopted an identical FMD protocol (5-min ischemia, distal cuff inflation), contemporary echo-Doppler methodology, and observer-independent automated analysis. Linear regression analysis was used to identify factors contributing to changes in FMD%. We found that cardiopulmonary fitness improved, and weight, body mass index (BMI), cholesterol, and mean arterial pressure (MAP) decreased after training, while FMD% increased in 76% of subjects (P < 0.001). Training-induced increase in FMD% was predicted by lower body weight (β = −0.212), lower baseline FMD% (β = −0.469), lower training frequency (β = −0.256), and longer training duration (β = 0.367) (combined: P < 0.001, r = 0.63). With the exception of a modest correlation with total cholesterol (r = −0.243, P < 0.01), changes in traditional cardiovascular risk factors were not significantly related to changes in FMD% (P > 0.05).In conclusion, we found that, while some subjects do not demonstrate increases following exercise training, improvement in FMD% is present in those with lower pretraining body weight and endothelial function. Moreover, exercise training-induced change in FMD% did not correlate with changes in traditional cardiovascular risk factors, indicating that some cardioprotective effects of exercise training are independent of improvement in risk factors.